Effect of plasma lipoprotein-associated phospholipase A2 levels on structure and function of heart in patients undergoing maintenance hemodialysis - WANG Yun-qian; CHEN Bao-ping; SHI Jun (Linchuang shenzangbing zazhi)
Objective To investigate the clinical application of plasma lipoprotein-associated phospholipase phospholipaseA2（Lp-PLA2） levels in evaluation of structure and function of heart in patients undergoing maintenance hemodialysis（MHD）.Methods Seventy MHD patients were involved in the study,who were treated with MHD for at least 6 months before the study and in a stable clinical status.The plasma Lp-PLA2 levels were examined by ELISA.The serum B-type natriuretic peptide（BNP） levels were measured by immunofluorescent assay.The parameters of left ventricular end-diastolic diameter（LVEDD）,left atrial diameter（LAD）,left ventricular posterior wall depth（LVPWD） and left ventricular ejection fraction（LVEF） were measured by cardiac color ultrasound,the left ventricular mass index(LVMD was calculated,and the relationship between plasma Lp-PLA2 levels and parameters determined by cardiac color ultrasound was analyzed.Another 40 healthy volunteers served as normal control group.Results（1） The levels of Lp-PLA2,BNP,LVMI,LVEF and systolic pressure in MHD group were significantly higher than those in normal control group（P<0.05）.（2） In MHD group,the patients with abnormal LVEF（LVEF<50%）,left ventricle hypertrophy and/or cardiac insufficiency（BNP>300 ng/L） had higher levels of Lp-PLA2 than the other patients without abnormal LVEF（LVEF>50%）,left ventricle hypertrophy and/or cardiac sufficiency（BNP<300 ng/L）.（3） The plasma Lp-PLA2 level was positively correlated with the levels of BNP（r =0.43,P<0.05） and LVMI（r = 0.58,P<0.01）,but negatively with the level of LVEF（r =- 0.67,P<0.01） in patients undergoing MHD.（4） Multiple stepwise regression analysis demonstrated that the plasmaLp-PLA2 level was correlated with the levels of LVMI（β=0.342,P<0.01）and LVEF（β=- 0.396,P<0.01）.Conclusions Higher plasma Lp-PLA2 levels extensively exists in patients undergoing MHD.Plasma Lp-PLA2 level can reflect structure and function of left ventricle,which may play an important role in the evaluation of left ventricular hypertrophy and function of left ventricle.